2008
DOI: 10.1007/s10865-008-9151-x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of mediators of change in the treatment of epilepsy with acceptance and commitment therapy

Abstract: The present study examined the mediators of change accounting for outcomes of a previously published study on acceptance and commitment therapy for the self-management of epilepsy and its life restricting impact. Conducted with 27 poor South Africans, a 9-h ACT protocol that included seizure management methods was shown to greatly reduce epileptic seizures and to increase quality of life over the next year as compared to an attention placebo control. A series of bootstrapped non-parametric multiple mediator te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
120
0
2

Year Published

2009
2009
2012
2012

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 169 publications
(136 citation statements)
references
References 42 publications
11
120
0
2
Order By: Relevance
“…Finally, this meta-analysis did not include an analysis of the putative treatment mediators. However, the proposed mediators are supported in the literature [6, 51]. For example, Forman et al [6] found that changes in ‘observing’ and ‘describing’ mediated outcome for CT but ‘experiential avoidance’, ‘acting with awareness’, and ‘acceptance’ mediated outcomes for ACT.…”
Section: Discussionmentioning
confidence: 95%
“…Finally, this meta-analysis did not include an analysis of the putative treatment mediators. However, the proposed mediators are supported in the literature [6, 51]. For example, Forman et al [6] found that changes in ‘observing’ and ‘describing’ mediated outcome for CT but ‘experiential avoidance’, ‘acting with awareness’, and ‘acceptance’ mediated outcomes for ACT.…”
Section: Discussionmentioning
confidence: 95%
“…Further, participants' level of values attainment and persistence in the face of barriers (as measured by the BullsEye) mediated improvements in frequency of seizures, overall well-being, and quality of life at a 1-year followup (Lundgren, Dahl, & Hayes, 2008).…”
Section: Empirical Support For the Process Of Values In Actmentioning
confidence: 94%
“…This has primarily been used in clinical settings to aid in values clarification and committed action. A second measure is the Bull's-Eye, which assesses values attainment, discrepancy between stated values and behavior, perceived barriers to valued living, and behavioral persistence (Lundgren, Dahl, Melin, & Strosahl, 2008) and has been shown to function well as an outcome measure and a process measure and as a tool for educating clients about values in a clinical context (Lundgren, Dahl, & Hayes, 2008;Lundgren, Dahl, Kies, & Melin, 2006;Lundgren, Dahl, Yardi, & Melin, 2008). The Personal Values Questionnaire (Blackledge & Ciarrochi, 2006) is an ACT-consistent modification of Sheldon et al's (2002) Measures of values-consistent behavior have thus far been assessed by self-report in the clinical domain, through the use of values homework sheets, the consistency portion of the Valued Living Questionnaire, or the Bulls-Eye diary.…”
Section: Empirical Support For the Process Of Values In Actmentioning
confidence: 99%
“…, smoking (Gifford, Kohlenberg, Hayes, Antonuccio, Piasecki, RasmussenHall, & Palm, 2004), diabetes management (Gregg, Callaghan, Hayes, & Glenn-Lawson, 2007), tinnitus (Westin, Andersson, & Hayes, 2008), weight (Lillis & Hayes, 2008), coping with epilepsy (Lundgren, Dahl, & Hayes, 2008), and coping with psychotic symptoms (Shawyer, Ratcliff, Mackinnon, Farhall, Hayes, & Copolov, 2007), among several others. So far, all of these specific versions work well in predicting outcomes within their respective areas and have been particularly effective as mediators of ACT interventions that target these specific problems (e.g., Gifford et al, 2004;Gregg et al, 2007;Lundgren et al, 2008;Lillis & Hayes, 2008).…”
mentioning
confidence: 99%
“…So far, all of these specific versions work well in predicting outcomes within their respective areas and have been particularly effective as mediators of ACT interventions that target these specific problems (e.g., Gifford et al, 2004;Gregg et al, 2007;Lundgren et al, 2008;Lillis & Hayes, 2008). However, a more general AAQ that can be used in a wide variety of contexts remains important for studying this theoretical model and the processes that underlie therapeutic and behavioral change.…”
mentioning
confidence: 99%